Polyethyleneimine-functionalized iron oxide nanoparticle-based method for isolation of Deoxyribonucleic Acid (DNA) from saliva samples in forensic investigations - Imran Khan; Gaurav Kaushik; Chaitenya Verma; Vinay Kumar; Richa Vashishtha (Egyptian Journal of Forensic Sciences, 2025)
Abstract Background Forensic investigations often rely on DNA analysis from biological samples such as saliva, which provides a non-invasive and accessible source of DNA. However, efficient isolation of high-quality DNA from saliva remains challenging due to the presence of inhibitors and mucins. In this study, a DNA isolation method was evaluated for isolating DNA from saliva samples using polyethyleneimine-functionalized iron-oxide nanoparticles, utilizing their high DNA binding capacity and the magnetic properties. Saliva samples (200 µL) were obtained from 20 healthy individuals, and DNA was isolated using PEI-IONPs followed by elution in 200 µL of elution buffer. DNA yield, purity, and integrity were assessed using UV–vis spectrophotometry and agarose gel electrophoresis. Results DNA isolated using PEI-IONP-based method showed an average yield of 5.8 µg per 200 µL of saliva, with an average concentration of 29.0 ng/µL. The purity ratio (OD260/OD280) of 1.82 indicated minimal contamination from proteins or RNA, and agarose gel electrophoresis confirmed the high molecular weight and integrity of the DNA. Conclusions This study establishes PEI-IONP as a reliable, safe, and efficient approach for DNA isolation from saliva samples, with potential applications in forensic science. The method also minimizes the use of hazardous chemicals, providing an environment friendly alternative to traditional isolation techniques. However, future research should evaluate the compatibility of the isolated DNA with PCR-based applications, such as STR profiling and mitochondrial DNA typing, comparing its recovery efficiency with established methods and validate its effectiveness with actual forensic casework samples, e.g., dried samples.